The spillover effects of water supply infrastructure development: A theoretical model - Naoyuki Yoshino; Santi Setiawati; Tifani Husna Siregar; KE Seetha Ram; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2023)
One of the main challenges in low-income Asia and the Pacific countries is users' willingness to pay for water services. In contrast, investors and private operators in the water sector prefer a high rate of return. This has often led to the failure of public-private partnerships for water projects. However, if we look at the overall picture of the development effects of water supply infrastructure, including spillover effects or externalities, the impacts are significant. One of the spillover effects of the development of water supply infrastructure could be the development of the region by inviting new businesses and creating new residential areas. Many people can move to a region where a good water supply is available. These new economic activities will increase tax revenues collected by the government. We develop a theoretical model of the spillover effects of water supply infrastructure developments. Our model shows how the incremental tax revenues that were previously absorbed only by the government could partly be shared with the investors and operators of the water supply infrastructure. Moreover, we propose a pooling system for collecting the incremental tax revenues attributable to the spillover effects in large cities and use them to support the service fee to build and operate systems in rural regions. Such a pooling system can accelerate the expansion of a nationwide network of water supply infrastructure that will quickly reduce the negative externalities and increase positive externalities for the nation.
Keywords: H20; H54; O18; Q25; 330; water supply infrastructure; infrastructure financing; spillover effect; Asia